THE PATTERN OF DNA SYNTHESIS IN THE CHROMOSOMES OF HUMAN BLOOD CELLS - German, James (The Rockefeller University Press, 1964)
The sequence in which various regions of the chromosomes of human blood cells complete DNA synthesis in vitro has been studied through the use of H(3)-thymidine labeling and autoradiography. Certain of its aspects have been defined, and these may serve as a basis for comparing the pattern of synthesis in cells of other tissues. In general, the long chromosomes continue replication later than the short ones. Variability of the sequence has been prominent. One pair from Group 13–15 and pair No. 17 complete replication early. In certain other chromosomes, replication is very active late in the S period, e.g. one X of the female cell, the Y of the male cell, two of Group 4–5, two of Group 13–15, the Nos. 16, and the Nos. 18. In the normal human female a striking correlation exists between the late replication of one of the X chromosomes, condensation during the intermitotic period, and presumed genetical inactivation. The pattern of replication characterizes certain chromosomes whose structural features alone are non-distinctive, and it may be useful in studies of cells in which a chromosomal aberration occurs.